THE EFFECTIVENES OF WORD MEMORIZATION METHOD USING DIGITAL BOOK TO IMPROVE STUDENTS’ VOCABULARY ACHIEVEMENT AT THE SIXTH GRADE OF SD KATOLIK SANG TIMUR PASURUAN - Glori Andriatmoko, Alvonsus (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2024)
This study aims to investigate whether the use of word memorization method using digital book provides a positive significant effect on the students’ vocabulary mastery. The quasi experimental research design was used in this study. The study included 49 sixth-grade English as Foreign Language (EFL) learners from a primary school, divided into two groups of 27 each. The experimental class was taught by word memorization method using digital book, while the control class was taught by using word memorization. The data of this study were collected through test in form of pre-test and post-test and calculated by using SPSS 20 Version. Based on the data analysis, the research finding showed that there was a significant difference between experimental class’s vocabulary score and control class’s vocabulary score. The researcher measured students’ post–test score by using independent sample t-test to know the difference between students who were taught by using word memorization method using digital book and students who were taught by using word memorization. The hypothesis verification was found by comparing the significance value (2-tailed) with the significance level 0.05. The estimation was: If the significance value > 0.05, Ha was rejected, it meant there was no significance positive effect. If the value < 0.05, Ha was accepted, it meant there was a significance positive effect. The mean score of vocabulary test done by the experimental class, based on the result of Independent sample t-test of post-test, was 79.52. Meanwhile, vocabulary test done by the control class, based on the result of Independent sample t-test of post-test, was 69.50. It meant that the implementation of word memorization method using digital book gave significant positive effect on students’ vocabulary mastery. Word memorization using digital book will abounding students’ creativity in developing various learning innovation, particularly on learning vocabulary.